AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BATANG SEREH, KULIT JERUK NIPIS DAN BULBUS BAWANG MERAH DAN KOMBINASINYA DENGAN PENISILIN TERHADAP STAPHYLOCOCCUS AUREUS DAN METHICILIN-RESISTANT STAPHYLOCOCCUS AUREUS - Nurfitriani Rizkiah, Ajeng
Nowadays, phenomena of antibiotic resistant bacteria increases rapidly. The use of herbs is often used by people as a primary therapy or companion of therapy with synthetic drugs. This study aimed to determine the antibacterial activity of the ethanol extract of stem lemongrass, lime peel and shallot bulbous and its combination with penicillin against Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus (MRSA). In this study, the antibacterial activity of the extracts was determined by its Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using microdilution method. Furthermore, the determination of the antibacterial activity combination of extravt with antibiotics was done by using checkerboard method and agar diffusion method. The results showed that MIC of stem lemongrass extract against Staphylococcus aureus and MRSA were 64 and 2048 µg/mL, respectively. The MICs of lime peel extract against Staphylococcus aureus and MRSA were 4096 and 8192 µg/mL, and for shallot bulbous extract were 128 and 4096 µg/mL, respectively. FICI value for the combination of lemongrass extract and penicillin against Staphylococcus aureus and MRSA were 0.1875 and 0.625, respectively. For a combination of lime peel extract and penicillin have FICI value against Staphylococcus aureus and MRSA were 1 and 1.5, respectively. Moreover, the value of FICI between extract of shallot bulbous and penicillin against Staphylococcus aureus and MRSA were 0.25 and 0.75, respectively. In conclusion, lemongrass extract has the lowest MIC compared with lime peel extract and shallot bulbous extract against Staphylococcus aureus and MRSA. Combination of lemongrass stem extract with penicillin and shallot bulbous extract with penicillin against Staphylococcus aureus and MRSA showed synergistic activity.